European student’s mathematical olympiad’ 09 - Dainius Dzindzalieta (Lietuvos Matematikos Rinkinys, 2009)
In this article we talk about Vojtech Jarn¸ kk International Mathematical Competition for students’ also called “Europe’09 student olympiad” which was held in Czech Republic, Ostrava. We also give some problems and one solution of not the hardest problem.